2006
DOI: 10.1016/j.jnucmat.2005.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxide films on primary water stress corrosion cracking initiation of alloy 600

Abstract: In the present study alloy 600 was tested in simulated pressurised water reactor (PWR) primary water, at 360°C, under an hydrogen partial pressure of 30 kPa. These testing conditions correspond to the maximum sensitivity of alloy 600 to crack initiation. The resulting oxidised structures (corrosion scale and underlying metal) were characterised. A chromium rich oxide layer was revealed, the underlying metal being chromium depleted. In addition, analysis of the chemical composition of the metal close to the oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
66
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(74 citation statements)
references
References 19 publications
(14 reference statements)
7
66
1
Order By: Relevance
“…However, blocky oxides of about 100 nm were found on the surface of 'Rod', while fine platelet oxides were found for 'Tube' and 'Plate'. It has been reported that the blocky oxides are Ni-Fe spinel oxides formed on top of Cr-rich oxide layer [22]. The presence of blocky oxides for 'Rod' could be correlated with the relatively poor protection of underlying Cr-rich oxide layer as they are known to be formed by Ni-Fe diffusion through the oxide layer [23].…”
Section: Suraface Oxides and Oxygen Penetrationmentioning
confidence: 99%
“…However, blocky oxides of about 100 nm were found on the surface of 'Rod', while fine platelet oxides were found for 'Tube' and 'Plate'. It has been reported that the blocky oxides are Ni-Fe spinel oxides formed on top of Cr-rich oxide layer [22]. The presence of blocky oxides for 'Rod' could be correlated with the relatively poor protection of underlying Cr-rich oxide layer as they are known to be formed by Ni-Fe diffusion through the oxide layer [23].…”
Section: Suraface Oxides and Oxygen Penetrationmentioning
confidence: 99%
“…As a kind of nickel-base alloys, Alloy C-276 has high mechanical strength and superior toughness in high temperature [19][20][21][22]. Besides, it is observed to have an excellent high-temperature corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation behavior of nickel-base alloys has been one of the hot topics because the oxide films formed are important to their performance. Up to now, in order to elucidate the oxidation process, some studies have been done to analyze the formed oxide films [2][3][4][5][6][7][8][9]. And the effects of different water chemistry parameters such as dissolved hydrogen (DH) [10][11][12][13][14], pH [15,16], temperature [15,17,18], Li concentration [19] and Zn injection [20,21] on the oxidation behaviors of Ni-base alloys have also been investigated.…”
Section: Introductionmentioning
confidence: 99%